FAKTOR RISIKO PERILAKU KELUARGA DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI INDONESIA: META ANALYSIS TAHUN 2015-2020 - Laste Menanti; R Azizah; Mohd Talib Latif; Acknes Leonita; Arif Sumantri; Siti N.A Jauharoh; Muhammad Addin Rizaldi (Dian Nuswantoro Semarang, 2022)
countries. The proportionate mortality rate (PMR) due to ARI in children under five in the world is 16%, two thirds of deaths are infant deaths. The purpose of this study was to analyze the risk factors for family behavior with the incidence of ARI in children under five in Indonesia. The method in this study uses meta-analysis to find the effect size value using JASP software version 0.9.2. Sources of data in this study came from Google Scholar, Science Direct, and Pubmed then sorted according to inclusion and exclusion criteria and obtained 37 research articles. The results of secondary data from the meta-analysis method found that the variable using mosquito coils had a 1.094 times greater risk of experiencing the incidence of ARI in toddlers. The conclusion from the results of the meta-analysis that has a higher level of risk on the family behavior variable is the family smoking habit variable. Efforts to control the risk of ARI in toddlers by conducting periodic counseling or promotion about the dangers of ARI disease, reducing the factors that influence the incidence of ARI in toddlers by providing good nutrition for the growth and development of infants, as well as communities or families who have toddlers to stop smoking, especially in the house or near.Keyword: ARI incidence, family behavior, and toddlers